Translating fathers' support for breastfeeding into practice. (3rd November 2021) - Baldwin, Sharin; Bick, Debra; Spiro, Alison
Abstract: Breastfeeding has numerous health benefits for the mother and child. For breastfeeding to be successful and continue for longer, women need adequate support. Fathers/partners play an important role in providing this support to women, but research suggests that fathers/partners often feel inadequately informed and supported by health professionals. Midwives and health visitors are in ideal positions to offer women and their partner's timely and relevant breastfeeding information and support throughout the perinatal period. This article discusses the benefits of breastfeeding, presents research evidence of the crucial role fathers/partners play in promoting and supporting breastfeeding, and recommends ways in which health professionals can provide breastfeeding information and support to fathers/partners.